(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Corporate Social Responsibility has gained much attention in recent years. Many professional bodies such as ACCA, CIMA, CIM and universities engage themselves in identifying the role of CSR in doing sustainable business. The importance of practice of CSR in sustainable business is inevitable throughout the world. Similarly, in India, the concept of CSR is gaining its momentum over the past few years. However, still companies are reluctant to embrace to CSR as it took long period of time in paying-off the investments they made. However, government of India has taken many initiatives to improve CSR among the Indians and companies operating in India. In order to do this and improve the level of CSR in India amendments has been done in the Company Law. In today’s scenario we need more attention of big corporate firms and companies to serve Nation and society. Being a socially responsible company can bolster a company’s image and build its brand too because social responsibility empowers employees to leverage the corporate resources at their disposal to do well. Formal Corporate Social Responsibility programs can boost employee morale and lead to greater productivity in the workforce.